Managerial Turnover and Strategic Change - Sliwka, Dirk (Management Science, 2007)
The connection between strategic change and managerial turnover is studied within a model where managers decide on a firm's strategy. Managers as well as firm owners care for the long-term success of a company, but managers are also interested in their own reputation. Due to reputational concerns, managers are reluctant to alter strategic decisions they themselves made in the past even when internal accounting information indicates that they should do so. It is shown that it may well be optimal in some cases to dismiss managers of higher ability while someone less talented may be kept in office when strategic change has to be enforced.